Implementing Wh-Questions Strategy To Improving Students’ Writing Ability On Facebook As The Teaching Media - Asnawan; Yovita Dyah Permatasari (International Journal of Educational Research & Social Sciences, 2021)
This study is categorized as a Classroom Action Research (CAR). The goal of this study is to improving the students’ writing ability by implementing WH-Question strategy through social media Facebook as the teaching media.   tenth grade students of The Islamic Senior High School of Walisongo Rowotengah  Sumberbaru - Jember academic year 2020/2021 to solved the students’ problems in writing a recount text. As the result of preliminary study indicated that the students’ problems toward their writing competence can be grouped into three problems: 1) Students’ writing was very low, 2) Students were not interested in learning English, 3) , the students faced a serious problem in arranging the sentences. Hence, the criteria of success were directed to the mention problems. Consequently, the students average in the Cycle I was 70.3, and 81.4 in the Cycle II. The findings revealed that by using WH Question strategy could improved the students’ writing skill of recount text through Facebook as the teaching media. In fact, WH-questions strategy became the interesting teaching and learning to make the students easier in understanding English skills. This concepts of teaching strategy could be applied in the classroom and also an online classes. Thus, students awarded new experiences, good communication of relationship, and they did the assignments with their own passions.